Metalloproteinases-2 and -9 predict left ventricular remodeling after myocardial infarction - Cogni, Ana Lucia [UNESP]; Farah, Elaine [UNESP]; Minicucci, Marcos F. [UNESP]; Azevedo, Paula S. [UNESP]; Okoshi, Katashi [UNESP]; Matsubara, Beatriz B. [UNESP]; Zanati, Silméia [UNESP]; Haggeman, Rodrigo [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Zornoff, Leonardo A. M. [UNESP] (Sociedade Brasileira de Cardiologia, 2013)
Background: The role of serum metalloproteinases (MMP) after myocardial infarction (MI) is unknown. Objective: The aim of this study was to evaluate the role of serum MMP-2 and -9 as predictors of ventricular remodeling six months after anterior MI. Methods: We prospectively enrolled patients after their first anterior MI. MMP activity was assayed 12 to 72 hours after the MI. An echocardiogram was performed during the hospitalization and six months later. Results: We included 29 patients; 62% exhibited ventricular remodeling. The patients who exhibited remodeling had higher infarct size based on creatine phosphokinase (CPK) peak values (p = 0.037), higher prevalence of in-hospital congestive heart failure (p = 0.004), and decreased ejection fraction (EF) (p = 0.007). The patients with ventricular remodeling had significantly lower serum levels of inactive MMP-9 (p = 0.007) and significantly higher levels of the active form of MMP-2 (p = 0.011). In a multivariate logistic regression model, adjusted by age, CPK peak, EF and prevalence of heart failure, MMP-2 and -9 serum levels remained associated with remodeling (p = 0.033 and 0.044, respectively). Conclusion: Higher serum levels of inactive MMP-9 were associated with the preservation of left ventricular volumes, and higher serum levels of the active form of MMP-2 were a predictor of remodeling 6 months after MI. (Arq Bras Cardiol. 2013;100(4):315-321).
Keywords: Matrix metalloproteinase; Myocardial infarction; Ventricular function; Left; Physiopathology